Evoluzione e persistenza dell’iconografia di Primo Carnera nella cultura popolare italiana: mitopoiesi plebea e propaganda fascista (Altre Modernità, 2015)
This essay focuses on the process of entrechment in the Italian collective imagination of the figure of Primo Carnera, World Heavyweight Champion from 1933 to 1934, and on the evolution of his image from the years of his first wins to the beginning of XXI century. More specifically, the essay makes visible how the mythization of Carnera had spontaneously developed long before the Italian press started to extol the successes of the boxer, and how the Fascism subsequently tried to appropriate the image of Carnera – modifying some of its fundamental traits – in order to use it as a powerful tool of regime’s propaganda, especially during the war years. In the end, the essay shows how the figure of Carnera regained favour after the fall of the fascist regime reappropriating (or, more rarely, being distorted of) its original traits.The study has been carried out through the comparison of a selection of cartoons, caricatures and illustration from the popular press dedicated to Carnera, official portrayals of him during the fascist regime and comic books more or less expressely inspired by the figure of the boxer.